PENGARUH KECERDASAN EMOSIONAL TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM MENYELESAIKAN MASALAH KONTEKSTUAL: SYSTEMATIC LITERATURE REVIEW - Dewanti, Aulia Nafa; Syamsuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to systematically examine the influence of emotional intelligence (EI) on students' mathematical communication skills in solving contextual problems through a Systematic Literature Review (SLR) approach based on PRISMA 2020 guidelines. Data were collected from Google Scholar, SINTA, and Scopus databases, covering 15 articles published between 2022–2026 that met the inclusion criteria. The analysis shows that all 15 studies consistently report a positive and significant influence of EI on mathematical communication skills, with correlation coefficients ranging from r = 0.49 to 0.68 and determination coefficients of R² = 0.38–0.46. Among the five EI indicators (Goleman, 1995), emotion management (self-management) is the most dominant factor (87% of studies), followed by self-motivation (80%), self-awareness (67%), empathy (60%), and social skills (53%). These findings confirm that the affective dimension, especially EI, plays an important role in the quality of students' mathematical communication in contextual problem solving.